2015
DOI: 10.2967/jnumed.115.163907
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT for the Early Evaluation of Response to Neoadjuvant Treatment in Triple-Negative Breast Cancer: Influence of the Chemotherapy Regimen

Abstract: Patients with triple-negative breast cancer (TNBC) have poor outcome when pathologic complete response (pCR) is not reached after neoadjuvant chemotherapy. Early prediction would be helpful. We evaluated the association between metabolic response after 2 cycles of neoadjuvant chemotherapy, pCR, and outcome in patients receiving 2 different anthracycline-based regimens (conventional and intensified). Methods: Of 77 consecutive TNBC patients, 23 received EC-D (4 cycles of epirubicin 1 cyclophosphamide followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 22 publications
2
20
0
1
Order By: Relevance
“…First, the sample size was small and the patient population was heterogeneous. Despite the small number, our cohort had representative distribution with subtype distribution and pCR frequency similar to other reports . Second, PET timing was variable.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…First, the sample size was small and the patient population was heterogeneous. Despite the small number, our cohort had representative distribution with subtype distribution and pCR frequency similar to other reports . Second, PET timing was variable.…”
Section: Discussionsupporting
confidence: 70%
“…In aggressive tumor subtypes (TNBC or HER2+), our findings on the prognostic role of PET parameter confirm and extend on previous reports. Despite contradicting results, the ability of SUV reduction to predict pCR and survival has been investigated in TNBC and HER2+ tumors. However, limited information is available on the relationship between survival and residual FDG uptake during or following NAC in these subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The current standard NAC in TNBC includes anthracycline-cyclophosmamide (AC) combination followed by taxanes, with dose-dense (dd) regimens suggested as potentially more efficient than standard doses (16). In TNBC patients treated by ddAC, we observed a pCR rate at surgery of 69% in patients predicted to be responders with 18 F-FDG PET/CT (decrease of the tumor SUV max after 2 cycles $ 65%) versus only 8% in predicted nonresponders (DSUV max , 65%) (14). Alternative treatment could be used in nonresponders with the aim to increase the pCR rate.…”
mentioning
confidence: 90%
“…Early treatment response assessment could also be of help in the TNBC subgroup. Several reports highlighted the high accuracy of the early change in the SUV max to predict pCR (11,12) and outcome (13,14) in TNBC patients. In another recent study, DSUV max outperformed tumor blood flow (15).…”
mentioning
confidence: 99%
“…Finding effective treatment targets for TNBC has proven difficult so far. TNBCs are reported to respond to neo-adjuvant chemotherapy, but overall, survival in patients with such tumors is still poor [2]. Next-generation sequencing of TNBC has suggested that actionable mutations occur in only a small subset of these cancers and do not completely predict survival [3].…”
mentioning
confidence: 99%